Experimental analysis of tribological performance of modified jatropha oil enriched with nanoparticle additives for machining application - Jamaluddin, N. A.; Talib, N.; A. Sani, A. S. (2021)
The intensified developments of the vegetable-based metalworking fluids have been growing rapidly due to the environmental and health issue of the utilization of the mineral based oil. The vegetable oils are a great potential substitution of the mineral based oil which has been explored in recent years due to their high biodegradability, renewability and low toxicity in comparable with mineral oil. Non-edible vegetable oil had attracted an attention of the researches in contrast with edible oil which significantly compete with the human food supply. The main focus of this study was to evaluate a new formulation of vegetable-based nanofluid from chemically modified jatropha oil (MJO) blended with hexagonal boron nitride (hBN), graphene and copper oxide (CuO) nanoparticles at 0.05 wt.% concentration. The physicochemical testing was carried out in term of kinematic viscosity, viscosity index and flash point and was compare with commercial synthetic ester (SE). The analysis of MJO mixed with nanoparticles in the perspective of it tribological has been performed through a four ball tribo testing to determine the coefficient of friction, mean wear scar diameter, friction torque, surface roughness and volume wear rate. The results showed that the tribological performance the MJO+0.05wt.% CuO exhibit lowest value in of coefficient of friction and friction torque followed by MJO+0.05wt.% graphene, MJO+0.05wt.% hBN and SE. Nevertheless, the MJO+0.05wt.% graphene and MJO+0.05wt.% hBN provided the significant improvement by providing the lowest value of the mean wear scar diameter and surface roughness respectively. It concluded that the modified jatropha oil enriched with nanoparticles had a great improvement on their tribological performance, hence it’s a highly potential substitution of the SE for machining process.